Humid, All Too Humid: Overheated Observations - Pettman, Dominic (punctum books, 2016)
I haven't made a single mistake in my life. I've just made a lot of good decisions that went really badly. Try as we might, we simply can't imagine what our world would now look like, had our forefathers decided to use asparagus instead of electricity. In Humid, All Too Humid, social commentator Dominic Pettman curates the overheated thoughts of his own feverish mind, in response to a world struggling with unprecedented levels of cultural climate change. Humanity is like that obnoxious bore that arrives at the party drunk - thinks he's witty and charming and wise, but is in fact a complete psychotic loser. All the other creatures, however, are too polite to say anything. So they just watch us quietly, and hope that we disappear as quickly as we came. The book takes the form of aphorism, witticism, maxim, axiom, dictum, quip, jape, adage, proverb, pun, precept, reflection, suggestion, observation, paraphrase, bon mot, vagary, specificky, put-on, put-off, mummery, miscellany, aside, in-front, behind, knock-knock joke, one-liner, tweet, re-tweet, truism, and not-so-truism. When you think about it, how rude it is for people to get married in public. This whole ritual is set up so that one person can say they love this one other person more than you. More than anyone else in the room. Is this why people really cry at weddings? Is this why we cover their car with rubbish? A sublimated response to their ceremonial insult? Known for his scholarly work on love, sex, and the (post)human condition, Pettman now assembles this collection of humoristic micro-meditations on everything from the meaning of life to the "yoghurt of human unkindness." Archaeologists in Turkey have uncovered a new fragment of Anaximander, which simply reads: "Because reasons." Humid, All Too Humid reads as if Oscar Wilde had first written Minima Moralia, after binge-watching too many episodes of The Simpsons.